Le rôle des initiatives privées dans le développement des TIC à Ziguinchor - Dieng Mbaye (Netcom)
Ziguinchor belongs to the most isolated administration’s area in Senegal. In this city, is slat or cut to the rest of Senegal by a foreign country : Gambia. Concerning the public development access for information communication (ICT), strong is the notice that there is an absence of a particular initiative from the state, either from the international’s cooperation. The private enterprise is the one who took the positives initiatives by putting some easy access to the ICT. And from this there’s a positive conclusion which come in the success of “Sud Informatique” incite others to entrenched themselves. From historical center of the city to the peripheral or small, there are some phone centers, cyber center and become some fundamentals structures of the space.